DETERMINASI PENINGKATAN SISTEM PENGENDALIAN INTERN: RELEVANSINYA DENGAN INFORMASI AKUNTANSI (Studi pada Koperasi di Kota Semarang) - Yulianti Yulianti; Nirsetyo Wahdi; Saifudin Saifudin (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2017)
The strategic role of Cooperatives and Small and Medium Enterprises (SMEs) in the midst of a national economic life, a fact that can not be denied any longer. The strategic role is primarily related to the amount, distribution and potential. In addition to being the life expectancy for most people of Indonesia, KUKM also capable of absorbing high enough jobs. The problem that arises is the need for internal control in a company. SAK ETAP expected use of small, medium, able to prepare its financial statements to obtain funds for business development. To achieve these objectives, the required system, particularly in securing wealth, maintain accuracy and to what extent the reliability of accounting data in the cooperative.The research method is done by collecting data used questionnaire method. The questionnaire was given to the cooperative supervisors each, totaling 91 supervisors of cooperatives in all cooperatives in the city of Semarang. Data were analyzed using SPSS.Results of this research are: 1) There is a positive and significant influence between the independence of the internal control supervisors, so that if the independence of the supervisory increase the cooperative's internal control will also increasingly baik. 2) There is a positive and significant influence between the competence of the internal control, so that when supervisory competence increases, the internal control co-operatives will also be baik. 3) There is no influence of the scope of work on internal control. The level of complexity of the scope of the labor inspectors are not always followed by the low height of the internal control cooperatives. 4) There is a positive and significant influence between accounting information system of internal control, so that when the accounting information system of internal control, the better the cooperative will also be better